Uptake of Climate-Smart Agriculture Through a Gendered Intersectionality Lens: Experiences from Western Kenya - Mungai, Catherine; Opondo, Maggie; Outa, George; Nelson, Valerie; Nyasimi, Mary; Kimeli, Philip (Springer, 2017)
This study conducted in western Kenya demonstrates how a gendered intersectionality lens can be used to explore how and the extent to which farming communities are coping with climate change. Results from a quantitative survey undertaken with 51 farmers and from 4 focused group discussions held with 33 farmers (19 males and 14 females) indicate that 85% of the respondents are willing to adopt climate-smart agriculture (CSA) interventions if constraining factors are resolved.This study reveals that farmers, regardless of whether they are male or female, are willing to adopt climate smart technologies and practices. However, factors such as ethnicity, education, age and marital status determine the levels of uptake of CSA technologies and practices. Looking at crops for instance, we find a high uptake (62.7%) of improved high yielding varieties (HYVs) amongst farmers with primary level education, meaning literacy levels influence adoption of practices. Analysis using age as a lens reveals that there is a high uptake among the youth and adults. Interestingly, the study site comprises of both the Luo and Kalenjin ethnic communities and even though they neighbor each other, we find a high rate of uptake among the Luo community due to existing social and cultural norms and practices related to farming. In conclusion, using a gendered intersectionality lens strengthens the argument for targeted interventions which focus on local needs and priorities while recognizing local contexts as informed by social, cultural and economic factors.